V. K. Semenchenko's book collection in stocks of the Central Scientific Library of the Ural Branch of the Russian Academy of Sciences - N. A. Mudrova (Библиосфера)
Preserving the historical-cultural heritage is an actual problem of fundamental scientific research. A special place in this heritage is the book culture including libraries - state, public, private, personal ones. Book collections of scientists refer to the special section of libraries. A holistic view of the outstanding researcher book collections allows complementing and enriching ideas about the researcher creative laboratory, as well as providing additional materials on the history of science, book culture and, even widly, the history of Russia. The article is devoted to the collection of books from the library of a Russian physicist-chemist, Professor of the Physical Faculty of Moscow State University, Doctor of Chemical Sciences, V. K. Semenchenko, who is a major specialist in chemistry of thermodynamics, theory of electrolyte solutions, surface tension. This study is research continuation carried on in the Central Scientific Library of the Ural Branch of the Russian Academy of Sciences (CSL UB RAS) to investigate scientific and cultural heritage of the Urals and Russi. The research methodological basis is modern concepts of the history of book business in a broad socio-cultural perspective using the following techniques: bibliographic, functional, analytical-thematic, paleographic, systematic, bio-bibliographic and others. The small collection of V. K. Semenchenko’s books (100 units) entered the collection of CSL UB RAS in 1993 under the mediation of Academician Vladimir Pavlovich Skripov, Director of the Institute of Thermophysics of the Ural Branch of the Russian Academy of Sciences, who was a former student and postgraduate of V. K. Semenchenko. The composition of the book collection is represented in the chart. There are many works of famous scholars, Rus- sian and Soviet classics of science of the XX century (books included in Digital Library «Russian Scientific Heritage») in V. K. Semenchenko’s collection. 42 volumes of the library have autographs of their owner V. K. Semenchenko. The books have inscriptions of authors, friends and relatives addressed to V. K. Semenchenko. The book collection uniqueness is evident due to book «Theory of atom» by of V. K. Semenchenko presented to the library by the researcher’s daughter. The book page-proofs (layout) were done in 1941. This book remained in a single copy. Many books and authors of V. K. Semenchenko’s books collection are of interest in terms of studying the history of the world science development. Thus, studying the book collection of a physicists contributes to investigating the acquisition history and stocks composition of CSL UB RAS, book culture, Russian and world science, and, in general, into the country historical and cultural heritage preservation.